Adaptation of subpopulations of the Norway spruce needle endophyte Lophodermium piceae to the temperature regime. Issue 12 (December 2019) - Müller, Michael M.; Hamberg, Leena; Morozova, Tatjana; Sizykh, Alexander; Sieber, Thomas
Abstract: Lophodermium piceae represents the most common Norway spruce needle endophyte. The aim of this study was to find out whether subpopulations of L . piceae in climatically different environments (in which Norway spruce occurs natively) are adapted to local thermal conditions. L . piceae 's ability for thermal adaptation was investigated by determining growth rates of 163 isolates in vitro at four different temperatures: 2, 6, 20 and 25 °C. Isolates were obtained between 1995 and 2010 from apparently healthy needles sampled in Finland, Poland, Switzerland, Italy and southeastern Siberia. The sampling sites represent seven climatically distinct locations. Results were evaluated in relation to the age and geographic origin of the isolate, in addition to the highest and lowest average monthly temperature of the sampling location. We found a significant correlation between the growth rate and the age of the isolate at 25 °C. Variation in growth rates between subpopulations was low compared to within subpopulations. Only at 2 °C did statistically significant differences between the average growth rates of subpopulations emerge. These results suggest that L . piceae covers the whole distribution area of Norway spruce but that generally the thermal reaction norm of its subpopulations has not changed according to local temperature ranges, despite high contrast in thermal conditions across this vast area. Therefore, it would appear that the thermal environment is not a crucial factor in assessing the fitness of this fungal species within the native range of Norway spruce.